Towards a national indicator for urban green space provision and environmental inequalities in Germany: Method and findings - Henry Wüstemann; Dennis Kalisch (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
Action 5 of the EU 2020 Biodiversity Strategy explicitly mentions that member states will map and assess the state of ecosystems and their services in their national territory by 2014 with the assistance of the Commission. Access to urban green is a key contributor to social and ecological functions in urban environments. However, in Germany - like in many other European countries - a national indicator measuring the provision of urban green on household and individual level is missing. This study develops a national indicator for urban green space provision and environmental inequalities in Germany on household and individual level. We investigate the provision of urban green by merging geo-coded household data from the German Socio- Economic Panel (GSOEP) and census population data with geo-coded data on land use from the European Urban Atlas (EUA) for German major cities with more than 100.000 inhabitants. Based on open green space standards applied in European urban city planning we de ne two variables measuring access to green: First, we estimate the distance to urban green measured as the Euclidean distance between the household and the nearest green-site in meters. Secondly, we calculate the coverage of urban green space around the households in square meters. Results of the distance analysis based on GSOEP data show a mean and median distance to public green space of 229:1m and 190:5m, respectively. The results further indicate that 93% of the German households have access to green space within a 500m and 74.1% within a 300m bu er around their location. The average green space provision in German major cities adds up to 8:1m2 per capita (median). Moreover, statistical analysis of the socio-economic background of the households shows di erences in urban green provision related to income, education, employment status, migration background and nationality. We also identify di erences in green space provision on the city level ranging from 10:6ha (city of Frankfurt/Oder) to 1:2ha (city of Schwerin) green space within 500m around the household. Distances to the nearest urban green also vary between cities ranging from 99m (city of Frankfurt/Oder) to 349m (city of Schwerin). The coverage of green space per capita ranges from 36m2 (city of Bergisch Gladbach) to 2:5m2 (city of Schwerin). We also provide a ranking of German major cities based on the green space provision on city level. The analysis further shows an unequal distribution of green within cities. The ndings provide helpful information for policy and planning to ensure an adequate green space provision and to eliminate related environmental inequalities in Germany.
Keywords: Q56; Q58; R14; R20; R52; 330; Urban Green; Indicator; Household and individual level; Geocoded data; Environmental inequities